TRAINING ON MAKING RUMPON AS FISH HABITAT FOR FISHERMAN IN UJONG BLANG VILLAGE LHOKSEUMAWE CITY - M Fauzan; B Bustami; Teuku Mudi Hafli; M Mukhlis; Syibral Malasyi; F Fasdarsyah (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2022)
Indonesia has a very diverse fishery resource potential, including large pelagic, small pelagic, demersal, penaeid shrimp, crabs, crabs, squid and reef fish. Fishery is one sector that is relied upon for Indonesia's future development, because it can provide an economic impact to some of Indonesia's population. The national capture fisheries are still characterized by small-scale capture fisheries. This can be proven by the existence of capture fisheries in Indonesia which is still dominated by small-scale capture fisheries, namely around 85%, and only around 15% is carried out by larger-scale fisheries. the use of fishing gear that is not environmentally friendly encourages over-exploitation of fishery resources. rumpon are a tool for collecting fish. The use of rumpon as fishing aids has long been recognized by Indonesian fishermen. The success of rumpon as fishing aids need not be doubted anymore, because rumpon are very effective as a tool to collect fish to make it easier to catch. The method used in this activity is to conduct counseling in the form of providing a theoretical view of the positive impact in the field of rumpon. After conducting counseling, the training will continue with how to make rumpon properly and correctly.